Attitudes of Young People to Job Searching through Social Media: Case of Slovakia - Helena Kajanová; Martin Sedláček; Veronika Soósová (Economics & Sociology)
Successful Processes and tools for job searching for different positions are changing in present time. Social media are more important in job searching than any time before. This article is dealing with attitude of young people to job searching through social media. We are focused in our research on university students. The main aim of the article is identify present importance of social media in job searching and behavior of students on social media and their attitudes to possibilities of job searching through social media. The research was done by questionnaire survey on the group of students of Faculty of Social and Economic Relations, Alexander Dubček University of Trenčín. The survey was conducted in March - April 2016. We formulate deductions; identify trends and the future of social media in job searching.